The nature of mathematical knowledge and the impact on the teacher conceptions - Cerón Álvarez, Diana Carolina; Mesa Laverde, Yuly Carolina; Rojas Morales, Clara Emilse (Universidad Pedagógica y Tecnológica de Colombia, 2012)
In this paper, it is shown clearly the way in which macro research is fed through college graduation work and through the consolidation of the theoretical referents around the nature of mathematics, fulfilling a historical and epistemological review of mathematics knowledge, that later on, will let to elaborate the mathematical categories, its teaching and learning and it is the basis for the designing of questionnaires, interpretative analysis of the compiled data in the study.